The Effect of Trade Openness, Foreign Direct Invest-ment (FDI) and Inflation on Gross Regional Domestic Product (GRDP) in Riau Province 2003 - 2022 - Ramadani, Fitri; Syapsan, Syapsan; Darmayuda, Darmayuda (Politeknik Negeri Bengkalis, 2024)
This research aims to investigate the effect of Trade Openness, Foreign Direct Investment (FDI), and Inflation on the Gross Regional Domestic Product (GRDP) in Riau Province 2003-2022. The analytical method employed is multiple linear regression analysis, specifically the Ordinary Least Squares (OLS) method, using E-Views 12 software. The simultaneous analysis results show that the variables Trade Openness, Foreign Direct Investment (FDI) and Inflation collectively have a significant impact on the GDP in Riau Province 2003-2022. Meanwhile, the partial analysis indicates that the variables Trade Openness, Foreign Direct Investment (FDI) have a positive effect and inflation has a negative effect on the GRDP in Riau Province.